Fused Thiopyrano[2,3-d]thiazole Derivatives as Potential Anticancer Agents - Kryshchyshyn, Anna (Österreichische Apotheker-Verlagsgesellschaft, 2012)
rel-(5aR,11bR)-3,5a,6,11b-tetrahydro-2H,5H-chromeno[4′,3′:4,5]thiopyrano[2,3-d][1,3]thiazol-2-ones formed by the stereoselective Knoevenagel-hetero-Diels-Alder reaction were functionalized at the nitrogen in position 3 via reactions of alkylation, cyanoethylation, and acylation. The synthesized compounds were evaluated for their anticancer activity in NCI60 cell lines. Among the tested compounds, 3f was found to be the most active candidate with the greatest influence on leukemia, non-small cell lung cancer, colon cancer, CNS cancer, melanoma, prostate cancer, and breast cancer subpanel cell lines with GI(50) values over a range of 0.37–0.67 μM.